Bee boy clash of the killer queens - De Saulles, Tony (Bee Boy, 2018)
"Half Bee. Half BOY. Melvin Meadly is ... Bee Boy. As a bee, Mel is ready to defend his hive against all enemies taking on killer wasps, terrifying hawkmoths, and battling queen bees. But as a boy, has he got what it takes to protect his bees (and himself) against the greatest menace of all--Nasty Norman Crudwell?"-- Back cover. Includes facts about bees.